THE ACCOUNTING EXCHANGE. - Vatter, William J.; Bornemann, Alfred; Zimering, Max; Moonitz, Maurice; de Roover, Raymond (The Accounting Review, 1946)
Abstract In this article the authors comment on an article related to placement of taxes in income statement, which was published in an earlier issue of the journal "The Accounting Review," as of January 1946. There are several kinds of revenue deductions which are nonetheless broadly in the same pew when it comes to the over-all calculation of net corporate income. First of the three classes of deductions is cost, in the sense of goods and services definitely consumed in the process of production. Second is losses, in the sense of outlays of one sort or another which have lost all significance so far as future operations are concerned, even though not having made any recognizable contribution in the past operations and last is taxes, which is payments to governmental units as computed on various bases and representing services only in the vague general sense in which government makes a contribution to the carrying on of the particular business enterprise. All of these classes of deductions are in the same boat when it comes to the question of determining profits.